Strategic Managerial Economics: Enhancing Financial Resilience and Business Growth - Noercholis Farizy (LifeSciFi, 2024)
Managerial economics plays a crucial role in guiding businesses toward financial sustainability and competitive advantage. This study conducts a systematic literature review to explore best practices in financial planning, investment strategies, and risk management within the context of managerial economics. By analyzing 20 studies published between 2012 and 2024 across multiple industries, key financial planning strategies such as budgeting, risk diversification, and technological investment are identified as essential for sustained growth. The findings highlight the importance of proactive economic management, digital transformation, and strategic decision-making in mitigating financial uncertainties. This review provides valuable insights for practitioners and researchers seeking to optimize business performance through effective economic managerial practices.